Finite Element Methods Problem 4.21 Part 2 : Understanding the Six-Step Finite Element Approach - Jones, Simon (McGraw-Hill's AccessEngineering., 2022)
This video provides a detailed introduction to Steps 3 (assembly of global equations) and 4 (identifying boundary conditions) of the six-step finite element approach.